Originally Posted by

**EricS** Good morning everyone, I am having some trobule with the following equation.

This is what I have done so far.

4x^2+6x-2=0

I am using ax^2+bx+c=0

so

a=4

b=6

c=-2

$\displaystyle x=\frac{-(6)\pm\sqrt{6^2-4(4)(-2)}}{2(4)}$

$\displaystyle x=\frac{-(6)\pm\sqrt{36+32}}{8}$

$\displaystyle x=\frac{-(6)\pm\sqrt{68}}{8}$

$\displaystyle x=\frac{-(6)\pm\sqrt{8.25}}{8}$

$\displaystyle x=\frac{-(6)+8.25}{8},\frac{-(6)-8.25}{8}$

$\displaystyle \frac{-14.25}{8},\frac{2.25}{8}$

Does this look right to you?